Pengaruh Celebrity Endorser dan Viral Marketing terhadap Keputusan Pembelian Melalui Minat Beli (Literature Review Manajemen Pemasaran) - Indah Anggraeni Purnama Sari; Shofwatun Hasna; Muhamad Agung Ali Fikri; Firdaus Putra; Dhaniel Hutagalung; Dwi Ferdiyatmoko Cahya Kumoro; Marhaendro Purno; Francisca Sestri Goestjahjanti; Mutiara Fitridiani; Winanti, Winanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to construct a conceptual synthesis regarding the influence of celebrity endorser and viral marketing on purchase decisions through purchase intention as a mediating variable within the domain of marketing management. The research adopts a non-empirical qualitative approach using a systematic literature review to integrate and critically analyze previous empirical findings and theoretical perspectives. The findings indicate that celebrity endorser attributes such as credibility, attractiveness, and congruence enhance consumer trust and perceived value, while viral marketing strengthens social validation and message diffusion in digital environments. Both variables influence purchase decisions indirectly by shaping purchase intention as a behavioral intention mechanism. The study provides a coherent conceptual framework that can guide future empirical research in digital marketing contexts.